Strength and Durability of a New Adhesive Bond to Superficial Dentin Using Etch and Rinse and Self-Etch Systems: An In Vitro Study - Safa Manafi; Ali Eskandari zadeh; Niloofar Shademan; Maryam Mofidi; Mona Norozy (Islamic Dental Association of Iran, 2016)
Background and Aim: Data regarding the efficacy of universal adhesives are limited. This study aimed to assess the durability of a universal adhesive bond to superficial dentin using etch and rinse and self-etch modes. Materials and Methods: In this in vitro, experimental study, 32 sound molars were randomly divided into two groups of Scotchbond Universal adhesive with two-step etch and rinse mode and Scotchbond Universal adhesive with one one-step self-etch mode as recommended by the manufacturer. Coronal part of teeth was restored with composite. The teeth were mounted in acrylic blocks and prepared according to the trimming protocol. The specimens were then randomly divided into two groups of immediate and 5000 thermal cycles and were then subjected to tensile load at a crosshead speed of 1mm/minute. Data were analyzed using two-way ANOVA. Results: The interaction effect of the two independent variables on microtensile bond strength was not significant (P=0.957). Bond strength in etch and rinse group was significantly higher than that of self-etch group (P<0.001). Bond strength in thermocycling subgroups was significantly higher than that of immediate subgroups (P=0.034). Conclusion: Etch and rinse mode was superior to self-etch mode for use of Scotchbond Universal, and thermocycling increased the bond strength of this adhesive.